O papel das normas de gosto como chave interpretativa para compreender fenômenos de escolha no mercado de food service - Larraín, Joaquín Ignacio Jiménez (2016)
This study aims to identify, through consumption in the food service market, how people choose among the different restaurant offers and if this choices reveal, on one front, habitus of class, and, on another, if they manifest expectations of social distinction. Starting with the assumption that eating out reveals a costume, as analyzed by Max Weber, or taste, as described by Talcott Parsons, or a habitus, as defined by Pierre Bourdieu, is about identifying it as a ritual that is able to lend charisma to the social class that practices it (Weber, Parsons)